2009
DOI: 10.1111/j.1365-2095.2008.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of dietary minerals during the early seawater phase increase vertebral strength and reduce the prevalence of vertebral deformities in fast-growing under-yearling Atlantic salmon (Salmo salarL.) smolt

Abstract: An earlier study demonstrated that under-yearling (0+) Atlantic salmon (Salmo salar L.) smolt had a lower vertebral mineral content and mechanical strength and higher prevalence of vertebral deformities than 1+ smolt during the early seawater (SW) phase. The present study aimed to examine if commercial extruded high-energy diets need to be supplemented additional minerals for proper bone mineralization and prevention of bone deformities in fast growing 0 + smolts. We studied vertebral morphology with radiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
141
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(156 citation statements)
references
References 42 publications
12
141
3
Order By: Relevance
“…However, Fjelldal et al, (2009a) found that both mineral content and strength of bone was reduced in fish belonging to the group that had the highest prevalence of deformities, indicating a relationship between deformities and bone mineral content.…”
Section: Accepted M Manuscriptmentioning
confidence: 92%
“…However, Fjelldal et al, (2009a) found that both mineral content and strength of bone was reduced in fish belonging to the group that had the highest prevalence of deformities, indicating a relationship between deformities and bone mineral content.…”
Section: Accepted M Manuscriptmentioning
confidence: 92%
“…Low mineral content and mechanical strength of the vertebrae have been associated with the development of vertebral anterior-posterior compression Fjelldal et al, 2007b;Fjelldal et al, 2009), which is the most common deformity in farmed Atlantic salmon and is usually restricted to the tail region of the vertebral column (Witten et al, 2005;Berg et al, 2006;Fjelldal et al, 2008). A compressed vertebra has a normal central part where the angle between the wall of the cone of the vertebra and the anterior-posterior axis is approximately 45 deg.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the observed effects cannot be contributed to growth rate alone since both LL and increasing temperature promoted growth. The observed values on vertebra standardized dorsoventral diameter (DDs) are within normal values for postsmolts (Fjelldal et al 2005(Fjelldal et al , 2009) and do not suggest pathological changes. Accordingly, Grini et al (2011) found that postsmolts at 16°C developed vertebra deformities, while postsmolts at 10°C did not.…”
Section: Discussionmentioning
confidence: 69%